2002
DOI: 10.1016/s0008-6363(02)00459-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of ten RGS proteins in human myocardium: functional characterization of an upregulation of RGS4 in heart failure

Abstract: The upregulation of RGS4 in failing human myocardium diminishes Gq/11-mediated signalling and can be involved in the desensitization of Gq/11-mediated positive inotropic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(83 citation statements)
references
References 39 publications
4
78
1
Order By: Relevance
“…In the past two decades, RGS proteins have received increasing interest as potential drug targets in numerous therapeutic areas, including cardiovascular disease, multiple CNS disorders and several types of cancer (Mittmann et al, 2002;Riddle et al, 2005;Hurst and Hooks, 2009;Sjögren et al, 2010). While GPCR signalling has been a major focus in drug development, traditional GPCR agonists and antagonists are often associated with side effects due to widespread expression of many receptors and lack of receptor selectivity of drugs.…”
Section: Why Target Rgs Proteins In Drug Discovery?mentioning
confidence: 99%
“…In the past two decades, RGS proteins have received increasing interest as potential drug targets in numerous therapeutic areas, including cardiovascular disease, multiple CNS disorders and several types of cancer (Mittmann et al, 2002;Riddle et al, 2005;Hurst and Hooks, 2009;Sjögren et al, 2010). While GPCR signalling has been a major focus in drug development, traditional GPCR agonists and antagonists are often associated with side effects due to widespread expression of many receptors and lack of receptor selectivity of drugs.…”
Section: Why Target Rgs Proteins In Drug Discovery?mentioning
confidence: 99%
“…RGS2-RGS5 are thought to be important in the heart (5,6), although their precise roles remain unclear. Human heart failure is associated with increased RGS4 expression, whereas expression of RGS2 is unchanged (7). Forced overexpression of RGS4 blunts G q -stimulated cardiac hypertrophy in rat neonatal cardiac myocytes (8) and intact hearts (9) and suppresses cardiac hypertrophy of transgenic mice lacking guanylate cyclase-A (natriuretic peptide-stimulated cyclase; ref.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated a complete lack of correlation between RGS4 messenger RNA and protein levels in metastatic breast cancer cells due to its rapid proteasomal degradation (10). Although it has been reported that RGS4 facilitates breast cancer invasiveness and growth both in vitro and in vivo, its function on the cell cycle has not been explored thus far (8). In the present study, breast cancer cell lines were transfected with a recombinant cDNA plasmid containing the open reading frame of RGS4.…”
Section: Discussionmentioning
confidence: 89%
“…Proteins of the RGS family modulate GPCR-mediated signals in cells (5). Among the >20 RGS proteins known to date, RGS4, a GAP for heterotrimeric Gq and Gi (7), is associated with regulation of the hypertrophic response in the failing human myocardium (8,9) and with the regulation of migration and invasion in breast cancer (10). RGS4 has an N-terminal Cys residue that is targeted for ubiquitin-dependent degradation by arginylation through the Arg/N-end rule pathway of protein degradation (11,12).…”
Section: Introductionmentioning
confidence: 99%